Asian Tiger Mosquito, Aedes albopictus (Skuse) (Insecta: Diptera: Culicidae) - Leslie Rios; James E. Maruniak (EDIS)
The Asian tiger mosquito, Aedes albopictus (Skuse), was first documented in the United States in Texas in 1985 (Sprenger and Wuithiranyagool 1986). A year later, the Asian tiger mosquito was found in Florida at a tire dump site near Jacksonville (O'Meara 1997). Since that time, this species has spread rapidly throughout the eastern states, including all of Florida's 67 counties (O'Meara 1997). The arrival of Aedes albopictus has been correlated with the decline in the abundance and distribution of the yellow fever mosquito, Aedes aegypti. This document is EENY-319, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004.